Examining the factors that influence the voluntary disclosure of information by consumers to commercial organizations - Themistocleous, Christos; Wagner, Christian; Smith, Andrew (My University, 2013)
Modern marketing is data driven, often by information provided by customers themselves. The pertinent use of customer data enables organizations to provide tailored offerings and communications. Data collection can be implicit (e.g. with the use of transactional data) or explicit (e.g. in response to questionnaires). The project described here is concerned with the latter where the consumer is made aware of the process (overt process) and can assess what is being divulged. The impetus for this research owes much to a changing environment in which consumer concerns and more restrictive legislations mean that implicit collection is under pressure. Moreover many companies have always required more explicit and interactive means of data collection. The project seeks to introduce a multi-dimension framework that will provide an anatomy of what influences the voluntary disclosure (explicit collection) of consumers to commercial organizations. The framework is based on three core themes. Psychological processes: This section includes the key concept of Disclosure management (Barnett; 2004) which is the cognitive process that consumers go through before disclosing (or not) certain information, together with its accompanying notions of Compensation for disclosure of information (Andrade et. al; 2002) and Loss of face (Dahl, et al; 2001). Relational processes. These seek to explain how interpersonal relationships influence the disclosure of information The concept of interpersonal relationships can be translated into the following three core variables: trust (Jarvenpaa, et al ;1999 Premazzi et al 2010) intimacy (Brock and Zhou ;2012, Laurenceau et al ;1998) and Relationships (Biggemann; 2012, Phillips et. al. ;2009) where the focus point of these parameters would be their association and influence on disclosure of truthful information. Instrumental factors. This work explores how consumers perceive different methods of data capture in terms of privacy-intrusiveness. The project will examine the perception of consumers towards parameters like structure of data-capturing questionnaires (Acquisti et al.; 2012, Zimmer et al; 2009), online vs. offline methods of data capture (John et al; 2011) while ensuring the minimization of false information and avoidance of disclosure (Robertshaw and Marr; 2005, Daniel R., et al; 2007). Findings from all three categories will be cross referenced with the demographic characteristics of consumers which will provide us with a comprehensive understanding of who discloses more information compared with others as well as why. The project’s methodology will employ a mixture of exploratory methods (depth and survey) in order to explore the relationship between the three core themes identified above and also how these relate to socio-demographic factors. The application of our framework and the generation of findings that provide answers to our core research questions i.e. “Who is more predisposed to disclosure and why?” will enable organizations to identify the appropriate methods to attract different individuals and formulate appropriate customer friendly strategies that will help them acquire (in a voluntary way) much needed non-transactional data or continue to derive consent for using transactional data for marketing purposes.
Keywords: Marketing Management; Information disclosure; Management